The standard for portfolio management - Project Management Institute (Newtown Square, Pa : Project Management Institute, 2013)
Presents an introduction to the processes of portfolio management, discussing how to identify business goals, develop strategy, evaluate environmental and risk factors and successfully complete project objectives. Offers the most up to date information regarding accepted practices in portfolio management and includes new materials.
"Approved American National Standard ANSI/PMI 08-003-2012"--Cover.
Includes bibliographical references and index.
oif 24/06/15
Loan
Keywords: Project management -- Standards